AN EXTENSION SYSTEM DEVELOPMENT OF SUGARCANE PRODUCTION FOR SUGAR EQUILIBRIUM SYPPLY AND DEMAND OF THAILAND - Hamarn, Thawat; Seesang , Sunan; Puripunpinyoo , Anucha; Pakoktom , Tiwa (Journal of Buddhist Anthropology, 2021)
The objectives of this research were to 1) analyze an equilibrium supply and demand of sugar at international level and domestic level Thailand, 2) analyze an equilibrium supply and demand of sugarcane production for sugar in Thailand, and 3) develop an extension system for farmers to meet an equilibrium supply and demand of sugarcane and sugar production. The mixed research method was applied with 3 steps according to the objectives. The equilibrium supply and demand of sugar were determined by using secondary data and analyzed by regression model and time series. An extension system development for farmers was divided into two stages, which included an interview of 3 prototype sugar factories which had successful extension method and survey of 14 factories. In-depth and questionnaires were applied to collect data from factory executive and extension personnel of the factory, sugarcane farmer institute committees, and contacted farmers of each factory. The qualitative data were summarized and quantitative data were analyzed by using descriptive statistics. The research results showed that 1) the world sugar export related to world sugar production and consumption, which sugar export of Thailand related to domestic sugar production and domestic consumption. 2) Sugar production of Thailand related to sugarcane production area, yield (ton per hectare), and commercial cane sugar index. Furthermore, sugarcane production efficiency was related to annual rainfall. The optimum sugarcane quantity for equilibrium supply and demand of sugar of Thailand and sustainable occupation for farmers, there should be an average of 98.173 million tons annually. 3) The extension system for farmers to meet the expected sugarcane production should have the collaboration for development and learning by organizing the farmer group and carried out an extension activity through the group. The sugarcane production to support the sugarcane farmers should be incorporation government agencies, factories and farmer institutes. The average demand of sugarcane farmers on sugarcane production extension systems from factories, government agencies and sugarcane farmer institutes was 4.29, 4.18 and 3.69, respectively.